2022
DOI: 10.4209/aaqr.220125
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Visibility in Seoul, South Korea, Based on Particulate Matter and Weather Data, Using Machine-learning Algorithm

Abstract: Visibility is an important indicator of air quality and of any consequent meteorological and climate change. Therefore, visibility in Seoul, which is the most polluted city in South Korea, was estimated using machine learning (ML) algorithms based on meteorological (temperature, relative humidity, and precipitation) and particulate matter (PM10 and PM2.5) data acquired from an automatic weather station, and the estimated visibility was compared with the observed visibility. Meteorological data, observed at 1-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Among the deep learning-based visibility estimation methods, most researchers apply classical CNN models to visibility estimation directly. For example, Ortega, Mu, and Wang et al [17,18,19,20] used CNN to estimate the visibility of images, and their method directly leverage the power of feature learning of CNN models and then put them into fully connected layers to map the learning features to different visibility levels. Giyenko [5] constructed a CNN model for visibility estimation and achieved an 84% accuracy on the visibility dataset where captured by Korean CCTV.…”
Section: B Visibility Estimation Methods Based On Deep Learningmentioning
confidence: 99%
“…Among the deep learning-based visibility estimation methods, most researchers apply classical CNN models to visibility estimation directly. For example, Ortega, Mu, and Wang et al [17,18,19,20] used CNN to estimate the visibility of images, and their method directly leverage the power of feature learning of CNN models and then put them into fully connected layers to map the learning features to different visibility levels. Giyenko [5] constructed a CNN model for visibility estimation and achieved an 84% accuracy on the visibility dataset where captured by Korean CCTV.…”
Section: B Visibility Estimation Methods Based On Deep Learningmentioning
confidence: 99%
“…Ortega, Mu, and Wang [17,18,19,20] used CNN to estimate the visibility range of a single image, but their methods directly applied deep learning to obtain "learned features" which lead to low accuracy of visibility estimation. Chincholkar [21] adds some "engineering features" to his method, such as the brightness and variance of the image, but the accuracy of visibility estimation is still low because the brightness and variance of the image are "common features" of the image rather than "specific features" of visibility.…”
Section: B Visibility Estimation Methods Based On Deep Learningmentioning
confidence: 99%
“…Aman et al (2022) reported two visibility events in the winter of 2014 and 2015 affected by the synergetic effect of particulate pollution and meteorology. Recently, visibility-related studies across the world have started using machine learning (ML) models for visibility prediction using particulate matter and meteorological variables as input data (Kim et al 2022a; Kim et al 2022b; Penov and Guerova 2023) and the importance of different features is identi ed by feature importance plots (Kim et al 2022a; Penov and Guerova 2023). However, feature importance has limited insights, as it does not give information about their directional relationship with visibility and interactive effects of different variables.…”
Section: Introductionmentioning
confidence: 99%